SWG5 regulates grain size and weight via sugar metabolism-mediated signaling in rice - Lu, Wenhui; Cai, Gaoyi; Xing, Yannan; Fu, Xingzhe; Zhou, Lingling; Tang, Yijun; Xu, Ran; Li, Yunhai; Wu, Lian (Frontiers in Plant Science, 2025)
Grain size significantly affects rice yield and quality. Although several genes that regulate grain size have been identified, their mechanisms remain unclear. In this study, we characterized the swg5 mutant, which has a smaller plant height, shorter panicles, and smaller grains compared to the wild type (WT). MutMap resequencing and gene knockout analysis identified SWG5, a gene encoding the kinesin-13a protein, a new allele of SRS3 that positively regulates grain length and weight. RNA sequencing analyses revealed that the SWG5 allele is involved in diterpenoid biosynthesis, amino sugar metabolism, and pentose-glucuronate interconversions. Furthermore, young panicles of the swg5 mutant exhibited decreased sucrose invertase activity as well as reduced sugar and starch content. These findings indicate that SWG5/SRS3 plays a significant role in sugar metabolism, influencing grain size and weight in rice. This research provides valuable insights into breeding rice varieties with improved yield and grain quality.